A Cost-Utility Analysis Comparing Immediate Oncoplastic Surgery with Delayed Oncoplastic Surgery in Smoking Breast Cancer Patients - Bloom, Joshua A.; Asban, Ammar; Tian, Tina; Sekigami, Yurie; Losken, Albert; Chatterjee, Abhishek (Annals of surgical oncology, 2021)
Background Oncoplastic reduction mammoplasty for smoking breast cancer patients committed to smoking cessation may be performed immediately (increasing smoking-related risk) or in a delayed fashion (increasing radiation-related risk). Objective Our aim was to examine the cost utility of immediate versus delayed oncoplastic reconstruction when operating on a smoking patient with breast cancer and macromastia with a long-term commitment to smoking cessation. Methods A literature review determined the probabilities and outcomes for the treatment of unilateral breast cancer with immediate or delayed oncoplastic surgery. Reported utility scores were used to estimate quality-adjusted life-years (QALYs) for varying health states. A decision analysis tree was constructed with rollback analysis to highlight the more cost-effective strategy, and an incremental cost-utility ratio (ICUR) was calculated. Sensitivity analyses were performed to validate the robustness of the results. Results Immediate oncoplastic surgery is associated with a higher clinical effectiveness (QALY) of 33.3 compared with delayed oncoplastic surgery (33.26), with a higher increment of clinical effectiveness of 0.07 and relative cost reduction of $3458.11. This resulted in a negative ICUR of −50,194, which favored immediate reconstruction, indicating a dominant strategy. In one-way sensitivity analyses, delayed reconstruction was the more cost-effective strategy if the probability of successful immediate reconstruction falls below 29% or its cost exceeds $29,611. Monte-Carlo analysis showed a confidence of 99% that immediate oncoplastic surgery is more cost effective. Conclusions Despite the risk of postoperative complications associated with smoking, immediate oncoplastic surgery is more cost effective compared with delayed oncoplastic surgery in which reconstructive surgery would occur after radiation.